Négociation de la distance : les circuits de communication et de représentation des intérêts locaux (monarchie et empire portugais, xviie et xviiie siècles) - Maria Fernanda Bicalho (Les Cahiers de Framespa)
This article focuses on three issues related to the negotiation of distance, communication channels, and the representation of local interests within the Portuguese pluricontinental monarchy. The first has to do with the main mechanism of political communication between the center of the monarchy and various overseas localities : the letters and complaints submitted by municipal councils to the Crown. The second concerns the representation of the colonial elites of the main overseas cities and villages during the meetings of the Portuguese Cortes, especially starting in the second half of the 17th century, after the Restoration, or the Portuguese independence from the Habsburg Catholic monarchy in 1640. Finally, the third is related to prosecutors sent from overseas municipalities to Lisbon to defend the interests and intentions of their elites.